Development of Glimepiride Loaded Sustained Release Microparticles Using Tubular Microreactor - Naik, Jitendra; Deshmukh, Rutuja; Rajput, Rahul; Mishra, Satyendra; Singh, Mukesh K. (Micro and Nanosystems, 2021)
Background: Glimepiride is a third-generation, oral anti-diabetic sulfonylurea drug, generally recommended for the treatment of type–II diabetes. A biocompatible polymer, Eudragit RS 100 is widely used for the preparation of targeted and time-controlled release of drugs. Glimepiride is encapsulated using Eudragit RS 100 for sustained release delivery. Objective: To develop sustained release microparticles of Glimepiride using microreactor technology to reduce the dosing frequency. Methods: Microreactor precipitation method was used to develop sustained release microparticles of Glimepiride. Plackett-Burman design was employed for the optimization of all the parameters including the inner diameter of silicon tubing, the flow rate of solvent as well as antisolvent, length of tubing and concentration of polymer, etc. Microparticles prepared were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, Scanning electron microscopy and in vitro drug release as well as release kinetics study. Results: Placket Burman design was found to be effective for comparing more than two parameters at a time and showed the effect of parameters on design. The parameters A, B, C, D, E and J synergistically affected the encapsulation efficiency. FE-SEM demonstrated the smooth and spherical nature of particles. Fourier transformed infrared spectroscopy showed the absence of chemical interaction between polymer and drug; X-ray diffraction results showed the decrease in crystallinity of pure drug when it was transformed into encapsulated drug-loaded microparticles. The sustained drug release was observed for 12 h. Conclusion: Prepared Glimepiride loaded sustained release microparticles followed the first-order release kinetics. The developed formulation could reduce dose frequency and improve patient compliance.
Keywords: microreactor